Rational identification of an optimal antibody mixture for targeting the epidermal growth factor receptor - Koefoed, K.; Steinaa, Lucilla; Soderberg, J.N.; Kjaer, I.; Jacobsen, H.J.; Meijer, P.-J.; Haurum, J.S.; Jensen, A.; Kragh, M.; Andersen, P.S.; Pedersen, M.W. (Informa UK Limited, 2011)
The epidermal growth factor receptor (EGFR) is frequently dysregulated in human malignancies and a validated target for cancer therapy. Two monoclonal anti-EGFR antibodies (cetuximab and panitumumab) are approved for clinical use. However, the percentage of patients responding to treatment is low and many patients experiencing an initial response eventually relapse. Thus, the need for more efficacious treatments remains. Previous studies have reported that mixtures of antibodies targeting multiple distinct epitopes are more effective than single mAbs at inhibiting growth of human cancer cells in vitro and in vivo. The current work describes the rational approach that led to discovery and selection of a novel anti-EGFR antibody mixture Sym004, which is currently in Phase 2 clinical testing. Twenty-four selected anti-EGFR antibodies were systematically tested in dual and triple mixtures for their ability to inhibit cancer cells in vitro and tumor growth in vivo. The results show that targeting EGFR dependent cancer cells with mixtures of antibodies is superior at inhibiting their growth both in vitro and in vivo. In particular, antibody mixtures targeting non-overlapping epitopes on domain III are efficient and indeed Sym004 is composed of two monoclonal antibodies targeting this domain. The superior growth inhibitory activity of mixtures correlated with their ability to induce efficient EGFR degradation.